COMPARISON OF ROBOTIC RADICAL PROSTATECTOMY VS LAPAROSCOPIC RADICAL PROSTATECTOMY ON PROSTATE CANCER PATIENT: A COMPREHENSIVE SYSTEMATIC REVIEW - Rifai Fauzi, M. Iqbal; Alemina Ramadhani Ginting, Karina Asysyifaa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Prostate cancer constitutes 3.8 of all cancer-related deaths in men. Radical prostatectomy stands as a standard surgical treatment for prostate cancer. Robot-assisted systems have emerged aiming to simplify the intricacies of complex laparoscopic procedures. Specifically, robot-assisted laparoscopic prostatectomy (RALP) has been proposed as a means to expedite the learning curve, potentially leading to quicker reductions in operative time compared to traditional laparoscopic techniques (LRP). This study aims to serve a comprehensive systematic review to compare laparoscopic radical prostatectomy (LRP) and robot-assisted laparoscopic prostatectomy (RALP) on prostate cancer based on literatures of the last 10 years. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 655 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Robot-assisted radical prostatectomy (RARP) offers advantages such as quicker recovery and comparable safety to laparoscopic radical prostatectomy (LRP). Studies show better urinary continence and potency outcomes with RARP. While PSM rates vary between RARP and LRP, further research is needed to understand their impact on recurrence. Despite challenges like the lack of tactile sensation in RARP, it remains a popular choice for prostate cancer treatment.